The commercialization of molecular biology: Walter Gilbert and the Biogen startup. (2nd January 2017) - Dick, Brian; Jones, Mark
Abstract: Recombinant DNA technology was invented in 1973. Within a few years, molecular biologists began developing practical applications and establishing private companies to exploit them commercially. In 1978, Harvard biologist Walter Gilbert, one of the leading figures in the field, joined the founding scientific advisory board of a Swiss biotech startup called Biogen. He later became the company's CEO. His participation helped Biogen recruit top scientific talent in the United States and Europe and encouraged many of his professional colleagues to follow his example and go into business. In this way, Gilbert became a linchpin in the formation of the contemporary biotechnology industry. Because his adventures in business were shaped by circumstances unique to the late twentieth century, Gilbert's case adds a distinctive point of reference to studies of academic entrepreneurship. It also points to internal contradictions and conceptual ambiguities in neo-institutional accounts of research privatization.